2022
DOI: 10.1101/2022.12.12.520086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved N- and O-Glycopeptide Identification using High-Field Asymmetric Waveform Ion Mobility Spectrometry (FAIMS)

Abstract: Mass spectrometry is the premier tool for identifying and quantifying site-specific protein glycosylation globally. Analysis of intact glycopeptides often requires an enrichment step, after which the samples remain highly complex and exhibit a broad dynamic range of abundance.Here, we evaluated the analytical benefits of high-field asymmetric waveform ion mobility spectrometry (FAIMS) coupled to nano-liquid chromatography mass spectrometry (nLC-MS) for analyses of intact glycopeptide devoid of any enrichment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…As mentioned in the introduction, these studies investigated the glycoproteome of three Burkholderia species, 23 TMT-labeled N-glycopeptides, 24 tryptic N-glycopeptides from α-1-acid glycoprotein, 25 and both N-and Oglycopeptides from depleted human serum. 26 In agreement with Alagesan et al, 26 we found that as sample complexity increased, the utility of FAIMS was more apparent. Further, we showed that when using CVs lower than −40 V, we identified shorter glycopeptides with a higher aliphatic index, similar to Izaham et al 23 Though, contrary to this study, we found that by using CVs higher than −40 V, the observed glycopeptides were significantly longer and with a smaller aliphatic index.…”
Section: ■ Conclusionsupporting
confidence: 90%
See 4 more Smart Citations
“…As mentioned in the introduction, these studies investigated the glycoproteome of three Burkholderia species, 23 TMT-labeled N-glycopeptides, 24 tryptic N-glycopeptides from α-1-acid glycoprotein, 25 and both N-and Oglycopeptides from depleted human serum. 26 In agreement with Alagesan et al, 26 we found that as sample complexity increased, the utility of FAIMS was more apparent. Further, we showed that when using CVs lower than −40 V, we identified shorter glycopeptides with a higher aliphatic index, similar to Izaham et al 23 Though, contrary to this study, we found that by using CVs higher than −40 V, the observed glycopeptides were significantly longer and with a smaller aliphatic index.…”
Section: ■ Conclusionsupporting
confidence: 90%
“…This sample had lower complexity when compared to the entire human proteome, which should allow more reliable search results while still providing a wider variety of peptide sequences. 30 In accordance with previous CV optimization in other studies, 20,21,23,25,26 we performed single CV experiments from −25 to −80 V in −5 V intervals, as well as a control experiment without FAIMS. To select settings for double and triple CV experiments, we compared glycopeptides identified from single CV experiments, where we found that 87% of identifications were found using CVs −40, −45, or −50 V. As such, a combination of these CVs were used for double and triple CV experiments (Figure S6).…”
Section: Recombinant Glycoprotein Mixturementioning
confidence: 90%
See 3 more Smart Citations